Controlled synthesis of FeNx-CoNx dual active sites interfaced with metallic Co nanoparticles as bifunctional oxygen electrocatalysts for rechargeable Zn-air batteries - Wu, Yi-jin; Wu, Xiao-hong; Tu, Teng-xiu; Zhang, Peng-fang; Li, Jun-tao; Zhou, Yao; Huang, Ling; Sun, Shi-gang (Applied catalysis. B, Environmental, 2020)
[Display omitted] •The formation mechanism of CoNx and FeNx dual active sites and the hollow carbon nanoshell is identified.•The H-Co@FeCo/N/C shows a mass activity of 6.8 A gcat−1 at 0.9 V for ORR and superior bifunctional oxygen electrocatalytic activity (ΔE = 0.698 V).•The synergistic catalytic effect of the atomically dispersed FeNx-CoNx dual active sites towards ORR was confirmed through DFT calculation. Efficient bifunctional oxygen electrocatalysts are essential for high-performance rechargeable Zn-air batteries (rZABs). Herein, a porous hollow carbon nanoshell (H-Co@FeCo/N/C) in which FeNx and CoNx metal sites are atomically dispersed and interfaced intimately with metallic Co nanoparticles was derived from pyrolysis of polydopamine-coated ZnCo-ZIFs adsorbed with Fe3+; the chemical interactions among different organic and metal species during the polymer-coating process was inverstigated; their role in regulating the size of the Co nanoparticles, the structure of the hollow carbon nanoshell and the formation of the FeNx-CoNx dual active sites was revealed. The H-Co@FeCo/N/C showed superior bifunctional oxygen electrocatalytic activity (ΔE = 0.698 V) and mass activity of 6.8 A gcat.−1 at 0.9 V, outperforming the commercial Pt/C/RuO2 catalysts or the Fe/N/C or Co/N/C counterparts. When assembled for rZABs, the H-Co@FeCo/N/C cathode displayed a long cycle life of 200 h (Egap of about 1.0 V@10 mA cm-2).